UV LED Light Efficiency in Aflatoxin M1 Reduction in Bovine Milk - Kluczkovski, Ariane Mendonça; Góes, Abrames; Santos, Karolina; Diogenes, Luiz C. G.; Corrêa, Lúcia; Araújo, Claudio F.; Junior, Augusto K. (Journal of Agricultural Studies, 2023)
Bovine milk is a food consumed by people of different age groups and especially by children, as it provides essential nutrients to the diet. In Brazil, milk is one of the most important products of Brazilian agriculture, being essential in the generation of employment and income. However, when there is contamination by toxic agents, such as aflatoxin (AFL) which is carcinogenic to humans and animals, there is a risk to the health of the consumer. Therefore, the objective of this work was to analyze the efficiency of the application of UV LED light as a tool to reduce aflatoxin M1 (AFM1) in bovine milk produced in the state of Amazonas, Brazil. Concerning time in 3-, 6- and 9-minutes, the reduction rates of 75.5, 97.3, and 94.1% were observed, respectively. The use of UV LED light was effective in reducing the concentration of AFL studied to be evaluated on a production scale.